Analisis Perwatakan Tokoh Utama pada Novel Hujan Karya Tere Liye: Kajian Psikologi Sastra - Nur Asikin; Septi Gumiandri (JURNAL EDUKASI NONFORMAL, 2023)
This study aims to describe and identify the character of the main character in the novel entitled "Rain" by Tere Liye. The method used in this study is a qualitative descriptive method. The data source in this study is a novel entitled “Rain” by Tere Liye. The data in this study are fragments of the story in the novel entitled "Rain" by Tere Liye. Data collection is done by observing and documenting methods. Where in the see method uses an advanced technique in the form of a note-taking technique. Documentation is done by taking fragments of the story in the novel and then collecting it in the form of data. Furthermore, the presentation of data analysis was carried out using descriptive methods or informal methods, namely presenting in ordinary words. The results of the study found several characteristics of the main characters in accordance with Freud's theory, namely as follows; in (1.) the id has a reckless, stubborn, disappointed character. (2.) The ego has no self-character, never gives up. (3.) The Super Ego has an honest, caring, patient, jealous character.